Nickel hydroxide and nickel molybdate composite material as well as preparation method and neutral electrolytic water hydrogen evolution application thereof
By using nickel hydroxide and nickel molybdate composite materials as catalysts in a neutral environment and preparing through electrochemical etching, the problem of insufficient activity and stability of the catalyst in neutral water decomposition reaction is solved, and low overpotential and High stability of electrolytic hydrolysis hydrogen analysis effect.
Patent Information
- Application Number
- CN202411279693.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-10
AI Technical Summary
In a neutral environment, the activity and stability of the water decomposition catalyst are poor, especially the overpotential of non-precious metal catalysts is high and unstable during the process of electrolyzing hydrogen production, which limits the large-scale application of electrolyzing water technology.
Using nickel hydroxide and nickel molybdate composite materials as catalysts, it is prepared by electrochemical etching on a nickel-based conductive substrate to form a composite material with good conductivity and strong adsorption ability to be used for electrolytic hydrogen analysis reaction under neutral conditions .
The composite material exhibits low overpotential and high stability in neutral water decomposition reaction, can operate at high current density for more than 1000 hours, significantly improving catalytic activity and stability, and has important application prospects.
Smart Images

Figure SMS_1 
Figure HDA0005041238900000011 
Figure HDA0005041238900000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of neutral water electrolysis hydrogen production catalysts, and in particular relates to a nickel hydroxide and nickel molybdate composite material, a preparation method thereof, and an application of neutral water electrolysis hydrogen evolution. Background Art
[0002] Hydrogen has high energy density and its combustion products are zero carbon and pollution-free. Therefore, it is considered to be a new energy carrier that can be used to solve the energy crisis and reduce dependence on fossil energy. At present, most industries use natural gas steam reforming and carbon gasification reactions to produce hydrogen. In the process, a large amount of greenhouse gases such as CO2 will be released, thereby exacerbating the greenhouse effect. The electrolysis of water to produce hydrogen can not only produce high-purity hydrogen, but also directly use electricity generated by renewable energy. It is a promising and sustainable high-purity distributed hydrogen production technology. In recent years, people have been committed to developing high-performance non-precious metal catalysts to improve the efficiency of electrolyzers while controlling production costs, and have made good progress. However, both acidic electrolyzers based on proton exchange membranes and alkaline electrolyzers based on anion exchange membranes require the use of highly corrosive electrolytes, which not only cause great pollution to the environment, but also cause serious damage to the electrolyzer. Therefore, the development of water splitting catalysts that can work efficiently under mild conditions is of great significance to the field of electrolysis of water to produce hydrogen. However, the current progress in the field of neutral water electrolysis is slow, mainly because in a neutral environment, the concentration of intermediate reactants in water decomposition is low, which is not conducive to the adsorption / activation of the reactants by the catalyst. Therefore, the rational design of catalyst components and the regulation of the electronic structure of the catalyst so that it can be efficiently used in neutral water decomposition technology will provide support for the large-scale application of water electrolysis.
[0003] The water splitting process consists of two half reactions: the hydrogen evolution reaction (HER) involving two electron transfer and the oxygen evolution reaction (OER) involving four electron transfer. The development of efficient catalysts for HER will greatly promote the development of the water splitting field. Although some precious metal catalysts such as (IrO2) and platinum (Pt) have been designed for neutral HER research and have achieved good results, the low earth reserves and high cost of precious metal elements are undoubtedly not conducive to the large-scale application of water electrolysis technology. Therefore, some non-precious metal catalysts including cobalt-based, nickel-based and iron-based catalysts have also been proposed and used in pH-neutral HER, but these catalysts have high overpotentials (10mA / cm 2 The overpotential is higher than 100mV at a current density of 100mV and the stability is poor (less than 50 hours), which is far from practical application. Among non-precious metal catalysts, nickel-based catalysts are considered to be a material with HER activity comparable to precious metals, but the reaction activity of the single nickel element in the neutral water decomposition reaction of nickel-based catalysts is not high enough, and the high current performance and stability are poor. Summary of the invention
[0004] The purpose of the present invention is to provide a nickel hydroxide and nickel molybdate composite material, a preparation method thereof and an application of the composite material in neutral water electrolysis for hydrogen evolution. The composite material has a stable structure, abundant active sites, good electrical conductivity and strong water adsorption capacity. When used for water electrolysis for hydrogen evolution reaction under neutral conditions, the composite material has a low overpotential and still has extremely strong stability under high current conditions, exhibits excellent catalytic activity and stability, and has important application prospects.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] Provided is a nickel hydroxide and nickel molybdate composite material, comprising a conductive substrate and a nickel hydroxide and nickel molybdate composite material in-situ grown on the conductive substrate, which is obtained by electrochemical etching on a nickel-based conductive substrate.
[0007] According to the above solution, the nickel-based conductive substrate is any one of metal nickel foam, metal nickel mesh, and metal nickel-iron foam.
[0008] According to the above scheme, the nickel hydroxide and nickel molybdate composite material is prepared by using a mixed solution of strong acid and molybdic acid as an electrolyte and a nickel-based conductive substrate as an anode to carry out an electrochemical etching reaction.
[0009] Preferably, a carbon rod is used as the counter electrode.
[0010] Preferably, the voltage of the electrochemical etching reaction is 1V-2V, preferably 1.25V-1.6V; the time is 100-500s, preferably 200-350s.
[0011] A method for preparing the above-mentioned nickel hydroxide and nickel molybdate composite material is provided, comprising the following steps:
[0012] A mixed solution of strong acid and molybdic acid is used as an electrolyte, a nickel-based conductive substrate is used as an anode, and a carbon rod is used as a counter electrode to carry out an electrochemical etching reaction, and a nickel hydroxide and nickel molybdate composite is in situ grown on the nickel-based conductive substrate to obtain a nickel hydroxide and nickel molybdate composite material.
[0013] According to the above scheme, after the reaction is completed, cool to room temperature, take out, wash and dry.
[0014] According to the above scheme, the concentration of the strong acid is 0.5-1.5 mol / L; the concentration of the molybdic acid is 0.05-1 mol / L.
[0015] According to the above scheme, the strong acid is any one of H2SO4, HNO3 and HCl.
[0016] According to the above scheme, the voltage of the electrochemical etching reaction is 1V-2V; preferably 1.25V-1.6V.
[0017] According to the above scheme, the electrochemical etching reaction time is 100-500s; preferably 200-350s.
[0018] According to the above scheme, during the electrochemical etching reaction, the silver chloride electrode is used as the reference electrode.
[0019] Provided is an application of the nickel hydroxide and nickel molybdate composite material in a hydrogen evolution reaction by electrolysis of water under neutral conditions.
[0020] According to the above scheme, the nickel hydroxide and nickel molybdate composite material is used as a hydrogen evolution electrode to carry out a water hydrogen evolution reduction reaction in a neutral three-electrode system.
[0021] Preferably, in the neutral three-electrode system, the carbon rod serves as the counter electrode and the calomel electrode serves as the reference electrode.
[0022] Preferably, in the neutral three-electrode system, the neutral electrolyte is phosphate, sulfate or chloride, and the concentration of the neutral electrolyte is 1-6 mol / L.
[0023] Compared with the prior art, the present invention is beneficial in that:
[0024] 1. The present invention provides a nickel hydroxide and nickel molybdate composite material, comprising a nickel-based conductive substrate and a nickel hydroxide and nickel molybdate composite material in situ grown on the nickel-based conductive substrate by electrochemical etching; wherein: the nickel hydroxide and the nickel molybdate respectively play the role of H + and OH - The adsorption of water is beneficial to the splitting of water, which promotes the two-electron transfer process in the hydrogen evolution reaction, and finally significantly improves the neutral water reduction performance of the electrode; the composite material has a stable structure, rich active sites, good conductivity, and strong water adsorption capacity. When used in the electrolysis of water for hydrogen evolution reaction under neutral conditions, the electrolysis of water has a strong adsorption capacity of 10 and 500 mA cm -2 The required HER overpotentials in neutral aqueous solution were as low as 30 and 374 mV at current densities of 500 mA cm -2 It can operate for more than 1000 hours at high current density without obvious attenuation of neutral water reduction performance, demonstrating excellent catalytic activity and stability, and has important application prospects.
[0025] 2. The present invention provides a method for preparing a composite material, which is prepared by electrochemical etching reaction using a mixed solution of strong acid and molybdic acid as an electrolyte and a nickel-based conductive substrate as an anode. The prepared nickel hydroxide and nickel molybdate composite material has a stable structure and exhibits excellent catalytic activity and stability as a neutral water reduction electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1The scanning electron microscope (SEM) images of the nickel hydroxide and nickel molybdate (denoted as E-NF) nanosheet arrays grown on the nickel foam substrate after the electrochemical etching reaction in Example 1 at different magnifications.
[0027] Figure 2 The transmission electron microscope (TEM) image and energy dispersive spectroscopy (EDS) element distribution diagram of Ni, Mo and O elements of the E-NF obtained in Example 1 are shown.
[0028] Figure 3 (a) is the X-ray diffraction (XRD) pattern of E-NF and NF; (b) is the Raman spectrum (Raman) comparison of E-NF before and after the reaction; (c) is the Ni 2p energy level diagram of the X-ray photoelectron spectroscopy (XPS) before and after the reaction of E-NF; (d) is the Mo 3d energy level diagram of the XPS of NiMo / CoMoO4.
[0029] Figure 4 The HER performance comparison of NiMo / CoMoO4 in neutral electrolyte (1 mol / L phosphate buffer (PBS)) and other samples: (a) is the linear sweep voltammetry (LSV) curve; (b) is the overpotential comparison diagram under different current densities; (c) is the HER performance diagram under different neutral environments; (d) is the electrochemical impedance spectroscopy (EIS).
[0030] Figure 5 This is the voltage stability curve of NiMo / CoMoO4 at high current density in neutral electrolyte (1 mol / L PBS). DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0032] The embodiment of the present invention provides a nickel hydroxide and nickel molybdate composite material, comprising a conductive substrate and a nickel hydroxide and nickel molybdate composite material in-situ grown on the conductive substrate, which is obtained by electrochemical etching on a nickel-based conductive substrate.
[0033] In one embodiment, the conductive substrate is any one of metal nickel foam, metal nickel mesh, metal nickel felt, metal nickel-iron foam, etc.
[0034] In one embodiment, the nickel hydroxide and nickel molybdate composite material is prepared by electrochemical etching reaction using a mixed solution of strong acid and molybdic acid as an electrolyte and a nickel-based conductive substrate as an anode.
[0035] The embodiment of the present invention also provides a method for preparing the above-mentioned nickel hydroxide and nickel molybdate composite material, comprising the following steps:
[0036] A mixed solution of strong acid and molybdic acid is used as an electrolyte, a nickel-based conductive substrate is used as an anode, and a carbon rod is used as a counter electrode to carry out an electrochemical etching reaction, and a nickel hydroxide and nickel molybdate composite is in situ grown on the nickel-based conductive substrate to obtain a nickel hydroxide and nickel molybdate composite material.
[0037] In one embodiment, the concentration of the strong acid is 0.5-1.5 mol / L; the concentration of the molybdic acid is 0.05-1 mol / L.
[0038] In one embodiment, the strong acid is any one of H2SO4, HNO3 and HCl.
[0039] According to the above scheme, the voltage of the electrochemical etching reaction is 1V-2V; preferably 1.25V-1.6V.
[0040] According to the above scheme, the electrochemical etching reaction time is 100-500s; preferably 200-350s.
[0041] In one embodiment, a silver chloride electrode is used as a reference electrode.
[0042] The embodiment of the present invention also provides an application of the nickel hydroxide and nickel molybdate composite material in a hydrogen evolution reaction by electrolysis of water under neutral conditions.
[0043] In one embodiment, the nickel hydroxide and nickel molybdate composite material is used as a hydrogen evolution electrode to carry out a water hydrogen evolution reduction reaction in a neutral three-electrode system.
[0044] In a preferred embodiment, in a neutral three-electrode system, the carbon rod serves as a counter electrode and the calomel electrode serves as a reference electrode.
[0045] In a preferred embodiment, in the neutral three-electrode system, the neutral electrolyte is phosphate, sulfate or chloride, and the concentration of the neutral electrolyte is 1-6 mol / L.
[0046] The following are specific embodiments.
[0047] Example 1
[0048] Provided is a method for preparing a composite material of nickel hydroxide and nickel molybdate, comprising the following steps:
[0049] A 1cm*2cm nickel foam was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was used as the anode, the carbon rod as the counter electrode, the silver chloride electrode as the reference electrode, and the mixed solution containing 1mol / L sulfuric acid and 0.1mol / L molybdic acid as the electrolyte. The cleaned nickel foam was placed in 60mL of the electrolyte and reacted for 300 seconds under the condition of 1.5V voltage by electrochemical etching. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain nickel hydroxide and nickel molybdate nanoblock catalysts grown on nickel foam (referred to as "E-NF").
[0050] Comparative Example 1
[0051] Provided is a method for preparing nickel hydroxide, comprising the following steps:
[0052] A 1cm*2cm nickel foam was placed in a 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15 minutes. Then the cleaned nickel foam was used as the anode, the carbon rod as the counter electrode, the silver chloride electrode as the reference electrode, and 1mol / L sulfuric acid as the electrolyte. The cleaned nickel foam was placed in 60mL of the electrolyte and reacted for 300 seconds at a voltage of 1.5V using an electrochemical etching method. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60°C for 4 hours to obtain a nickel hydroxide catalyst grown on the nickel foam (referred to as "H-NF").
[0053] Figure 1 The E-NF obtained in Example 1 is as follows: the prepared catalyst is observed on JEOL JSM-7900, and the electron beam intensity is 12.6 keV. It can be seen that the prepared catalyst has a micron block structure of nickel hydroxide and nickel molybdate, and the size of the micron block is 0.5-2 μm.
[0054] Figure 2 This is the EDS element distribution diagram of the E-NF catalyst prepared in Example 1. The specific steps are to observe the morphology of the prepared catalyst on JEOL 2100F, and use energy dispersive spectroscopy equipped with QUANTAX 200-TEM model to study the distribution of each element in the catalyst. It can be seen that Ni, Mo and O elements are all distributed on the catalyst, successfully proving that Mo is incorporated into the catalyst.
[0055] Figure 3(a) is the XRD pattern of the prepared E-NF catalyst, specifically, the prepared catalyst was collected on X'Pert PRO. It can be seen that the characteristic peaks on the XRD pattern match those of α-phase nickel hydroxide (PDF#38-715), nickel molybdate (PDF#48-1745) and nickel foam (PDF#4-850), indicating the successful synthesis of nickel hydroxide and nickel molybdate composite materials.
[0056] The prepared catalyst samples were charged at 500 mA / cm 2 Raman characterization of the sample after 1000 hours of continuous hydrogen evolution reaction at a current density of Figure 3 (b) shows the comparison of Raman spectra of the sample before and after the hydrogen evolution reaction. The specific steps are to collect Raman spectrum signals on the HORIBA LabRAM with a laser wavelength of 832nm. It can be found that the sample has characteristic peaks belonging to Ni-O and Mo-O, indicating the successful introduction of NiMoO4 and Ni(OH)2.
[0057] Figure 3 (c) shows the XPS Ni 2p energy level spectrum comparison of the sample before and after the hydrogen evolution reaction. It can be found that after the reaction, the Ni 2+ The peak moves toward lower energy, indicating that the Ni element is being reduced during the reaction, and the Ni element gains electrons, which promotes the splitting of water.
[0058] Figure 3 (d) shows the comparison of the Mo 3d energy level spectra of the XPS before and after the hydrogen evolution reaction. The 3d split peak spacing of Mo before the reaction is 3.74 eV, indicating that the oxidation state of the Mo element is +6. In the sample after the continuous hydrogen evolution reaction, the Mo element has two valence states, +4 and +6. This is because the hydrogen evolution electrode will continuously gain electrons in the electrolysis of water, thereby reducing the valence state of the catalyst. The Mo element attracts electrons due to its strong electronegativity, making the electronic state around the metal Ni site stable, ensuring that the active site of the catalyst will not reduce its activity due to a significant reduction in the metal valence state, indicating the excellent stability of the material. The specific steps for collecting XPS spectra are to collect XPS signals on the ESCALAB 250XI (Thermo) system.
[0059] The E-NF catalyst prepared in Example 1 was tested for neutral water reduction reaction performance. The steps are as follows: a three-electrode system consisting of an E-NF catalyst as a working electrode, a silver chloride electrode as a reference electrode, and a graphite rod electrode as a counter electrode was placed in a neutral electrolyte to test its water reduction performance, wherein the electrolyte was a 1 mol / L phosphate buffer solution with a solution pH of 7.
[0060] Figure 4(a) and (b) show the linear sweep voltammetry (LSV) curves of E-NF, H-NF, NF (nickel foam) and Pt / C samples in 1 mol / L phosphate buffer solution and detailed HER overpotential comparison diagrams. It can be found that the HER performance of E-NF is significantly improved at 10 and 500 mA / cm 2 At a current density of 10 mA / cm2, the required HER overpotential is only as low as 30 and 374 mV, which is much better than the commercial Pt / C sample. The activity of the comparative H-NF is significantly worse than that of the E-NF. In addition, although the H-NF sample is 2 The overpotential is lower than that of Pt / C electrode at a current density of 500 mA / cm 2 At high current density, the performance of the H-NF sample is significantly lower than that of the Pt / C electrode (666mV vs. 593mV). This indicates that the introduction of Mo is necessary, and the synergistic effect of the two components promotes water splitting. The overpotentials of these samples in different neutral solutions are further calculated. Figure 4 (c) shows the E-NF sample, indicating that E-NF is beneficial to promote faster HER reaction kinetics. At the same time, the conductivity of E-NF promotes rapid electron transfer on the catalyst, as shown in Figure 4 (d) The electrochemical impedance spectroscopy shows that E-NF has a smaller charge transfer resistance.
[0061] Figure 5 The E-NF sample was shown in 1 mol / L PBS solution at 500 mA / cm 2 Stability under current density. E-NF sample in 1 mol / L PBS solution at 500 mA / cm 2 Stability under current density. At 500mA / cm 2 At a high current density, the E-NF sample can operate stably for more than 1000 hours, demonstrating its excellent stability.
[0062] Example 2
[0063] Provided is a method for preparing a composite material of nickel hydroxide and nickel molybdate, comprising the following steps:
[0064] Nickel foam of 1cm*2cm size was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was used as anode, carbon rod as counter electrode, silver chloride electrode as reference electrode, and a mixed solution containing 1.4mol / L nitric acid and 0.7mol / L molybdic acid as electrolyte. Then the cleaned nickel foam was placed in 60mL electrolyte and reacted for 400 seconds under 1.8V voltage by electrochemical etching. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain nickel hydroxide and nickel molybdate nanoblock catalysts grown on nickel foam.
[0065] The prepared nickel hydroxide and nickel molybdate nanoblock catalysts were used as working electrodes, a silver chloride electrode was used as a reference electrode, and a graphite rod electrode was used as a counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 3 mol / L sodium sulfate.
[0066] The sample was tested at 10 and 500 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0067] Example 3
[0068] Provided is a method for preparing a composite material of nickel hydroxide and nickel molybdate, comprising the following steps:
[0069] Nickel foam of 1cm*2cm size was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was used as anode, carbon rod as counter electrode, silver chloride electrode as reference electrode, and a mixed solution containing 0.5mol / L sulfuric acid and 0.05mol / L molybdic acid as electrolyte. Then the cleaned nickel foam was placed in 60mL electrolyte and reacted for 100 seconds under 1V voltage by electrochemical etching. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain nickel hydroxide and nickel molybdate nanoblock catalysts grown on nickel foam.
[0070] The prepared nickel hydroxide and nickel molybdate nanoblock catalysts were used as working electrodes, silver chloride electrodes were used as reference electrodes, and graphite rod electrodes were used as counter electrodes to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 3 mol / L sodium sulfate. 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0071] Example 4
[0072] Provided is a method for preparing a composite material of nickel hydroxide and nickel molybdate, comprising the following steps:
[0073] Nickel foam of 1cm*2cm size was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was used as anode, carbon rod as counter electrode, silver chloride electrode as reference electrode, and a mixed solution containing 0.75mol / L hydrochloric acid and 0.08mol / L molybdic acid as electrolyte. Then the cleaned nickel foam was placed in 60mL electrolyte and reacted for 200 seconds under 1.25V voltage by electrochemical etching. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain nickel hydroxide and nickel molybdate nanoblock catalysts grown on nickel foam.
[0074] The prepared nickel hydroxide and nickel molybdate nanoblock catalysts were used as working electrodes, a silver chloride electrode was used as a reference electrode, and a graphite rod electrode was used as a counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 3 mol / L sodium sulfate.
[0075] The sample was tested at 10 and 500 mA / cm 2 The overpotential of neutral water reduction at current density is shown in Table 1.
[0076] Example 5
[0077] Provided is a method for preparing a composite material of nickel hydroxide and nickel molybdate, comprising the following steps:
[0078] Nickel foam of 1cm*2cm size was placed in 3mol / L hydrochloric acid solution, anhydrous ethanol and deionized water for 15mins, and then the cleaned nickel foam was used as anode, carbon rod as counter electrode, silver chloride electrode as reference electrode, and mixed solution containing 1.2mol / L sulfuric acid and 0.4mol / L molybdic acid as electrolyte. Then the cleaned nickel foam was placed in 60mL electrolyte and reacted for 350 seconds under 1.6V voltage by electrochemical etching. After the reaction was completed and cooled to room temperature, the catalyst was repeatedly rinsed with anhydrous ethanol and deionized water, and then dried in an oven set at 60℃ for 4 hours to obtain nickel hydroxide and nickel molybdate nanoblock catalysts grown on nickel foam.
[0079] The prepared nickel hydroxide and nickel molybdate nanoblock catalysts were used as working electrodes, a silver chloride electrode was used as a reference electrode, and a graphite rod electrode was used as a counter electrode to form a three-electrode system and placed in a neutral electrolyte to test its water reduction performance. The electrolyte was 3 mol / L sodium sulfate.
[0080] The sample was tested at 10 and 500 mA / cm 2The overpotential of neutral water reduction at current density is shown in Table 1.
[0081] Table 1. Summary of neutral water reduction performance of NiMo / CoMoO4 samples prepared in Examples 1-5
[0082]
[0083] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A composite material of nickel hydroxide and nickel molybdate, characterized in that: The invention comprises a conductive substrate and a nickel hydroxide and nickel molybdate complex in-situ grown on the conductive substrate, and is obtained by electrochemical etching on the nickel-based conductive substrate.
2. The composite material of nickel hydroxide and nickel molybdate according to claim 1, characterized in that: The nickel-based conductive substrate is any one of metal nickel foam, metal nickel mesh, and metal nickel-iron foam.
3. The composite material of nickel hydroxide and nickel molybdate according to claim 1, characterized in that: The nickel hydroxide and nickel molybdate composite material is prepared by using a mixed solution of strong acid and molybdic acid as an electrolyte and a nickel-based conductive substrate as an anode to carry out an electrochemical etching reaction.
4. A method for preparing the composite material of nickel hydroxide and nickel molybdate according to any one of claims 1 to 3, characterized in that: The following steps are involved: A mixed solution of strong acid and molybdic acid is used as an electrolyte, a nickel-based conductive substrate is used as an anode, and a carbon rod is used as a counter electrode to carry out an electrochemical etching reaction, and nickel hydroxide and nickel molybdate are in situ grown on the nickel-based conductive substrate to obtain a nickel hydroxide and nickel molybdate composite material.
5. The preparation method according to claim 4, characterized in that: The concentration of the strong acid is 0.5-1.5 mol / L; the concentration of the molybdic acid is 0.05-1 mol / L.
6. The preparation method according to claim 4, characterized in that: The strong acid is any one of H2SO4, HNO3 and HCl.
7. The preparation method according to claim 4, characterized in that: The voltage of the electrochemical etching reaction is 1V-2V, and the time is 100-500s.
8. The preparation method according to claim 7, characterized in that: The voltage of the electrochemical etching reaction is 1.25V-1.6V, and the time is 200-350s.
9. Use of the nickel hydroxide and nickel molybdate composite material according to any one of claims 1 to 3 in hydrogen evolution reaction under neutral conditions by electrolysis of water.